Sustentabilidade nas organizações do terceiro setor filiadas à rede Pernambuco voluntário - PINTO, Natália Lúcia da Silva (2019)
Third-sector organizations are challenged by organizational sustainability in the continuity of service delivery. The objective of this research is to analyze the organizational sustainability of the Non-Governmental Organizations affiliated with the Pernambuco Voluntary Network. For this purpose, the following specific objectives were established: a) identify the profile of the institutions belonging to Rede Pernambuco Voluntário; b) verify the forms used to achieve sustainability in the chosen institutions for the study and the moments in which the activities were affected in function of the organizational sustainability; c) characterize performance measurement and sustainability assessment tools suited to Third Sector organizations; d) describe the contributions of the participations in the Pernambuco Voluntary Network. The research was based on the concepts of third sector, sustainability in the third sector, indicators of performance in the third sector and networks in the third sector. In order to conduct the research, a systematic review of the literature was adopted as a method of data collection to define the categories of analysis to compose the field research, which included the application of questionnaires and interviews. In addition, the research is qualitative, exploratory and descriptive, and used content analysis to analyze the data. The results indicated financial sustainability as the main way for organizations to carry out their activities; the effort to achieve sustainability is employed by most organizations and is manifest in the collective behavior of care for the common good and the continuous management of resources; financing by civil society, and the adoption of campaigns which are a successful experience of non-governmental organizations; the use of performance measurement and sustainability assessment tools lacks structuring and regularity in their application; the contribution of the Rede Pernambuco Voluntário for the visibility of the organization and the recruitment of volunteers to the detriment of the members' awareness that the Rede is a collective work belonging to its members. It was concluded that the organizations studied have difficulties to remain sustainable and need investments to continue working. The Network lacks a governance work so that it can fulfill its objectives effectively. Finally, the alignment between the systematic review of the literature and the research of allowed to consider that the categories of analysis used can constitute bases for the analysis of the sustainability in the organizations of the third sector.